Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445662
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Reactions Outside the Home: Challenges, Strategies, and Opportunities to Enhance Dining Out Experiences of People with Food Hypersensitivities

Abstract: People with food hypersensitivities experience adverse reactions when eating certain foods and thus need to adapt their diet. When dining out, the challenge is greater as people entrust the care of their allergy, intolerance, or celiac disease, in the hands of staff who might not have enough knowledge to appropriately care for them. This interview study explored how people with food hypersensitivities avoid reactions while eating out, to inspire future digital technology design. Our findings show the social an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Nowadays, especially among youth, dining outside the home at restaurants and cafes is a popular pastime, and dependency on and craving of convenience foods and fast foods have rapidly increased [19]. Even though the event of dining out provides an opportunity for social bonding, relaxation, and convenience, it may cause health problems for individuals with food allergies [20]. A survey conducted in 2020 across eight European countries on the effects of having a peanut allergy reported that around 89% of subjects felt restricted by the allergy; in terms of dining out and selecting a destination, 65% felt isolated while 90% felt tense about the whole procedure [21].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, especially among youth, dining outside the home at restaurants and cafes is a popular pastime, and dependency on and craving of convenience foods and fast foods have rapidly increased [19]. Even though the event of dining out provides an opportunity for social bonding, relaxation, and convenience, it may cause health problems for individuals with food allergies [20]. A survey conducted in 2020 across eight European countries on the effects of having a peanut allergy reported that around 89% of subjects felt restricted by the allergy; in terms of dining out and selecting a destination, 65% felt isolated while 90% felt tense about the whole procedure [21].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, consumers with adverse food reactions expect allergens to be identified on restaurant menus (Begen et al, 2018;Kwon et al, 2020). However, previous literature has shown that restaurants rarely list food allergens for each meal on the menu (Endres et al, 2021;Lee and Barker, 2017;Lee and Xu, 2015;Nunes et al, 2021). While consumers with food allergies value menu transparency, restaurants seem to be insensitive to the needs of this group of consumers.…”
Section: Dining Out With Adverse Food Reactionsmentioning
confidence: 99%
“…However, previous literature has shown that restaurants rarely list food allergens for each meal on the menu (Endres et al. , 2021; Lee and Barker, 2017; Lee and Xu, 2015; Nunes et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, the type of food selected may depend on mood [3], people choose different types of food and drinks depending on how they are feeling (e.g., anxious, sad, happy). Additionally, the social context is also an important factor for food selection and experience such as eating alone or with other people, cultural ideals, personal factors and resources [4], and some have diet restrictions that modifies their capability to socialize in restaurants [19].…”
Section: Eating Experience In Hcimentioning
confidence: 99%